2017
DOI: 10.3389/fphys.2017.00377
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training Decreases Inflammation and Increases Cognition and Physical Fitness in Older Women with Cognitive Impairment

Abstract: Introduction: Cognitive impairment that affects older adults is commonly associated with an inflammatory imbalance, resulting in decreased physical fitness. Exercise has been pointed to mitigate immunosenescence and cognitive impairment associated with aging, while increase in physical fitness. However, few studies explored the relationship between changes in cytokine concentration and improvement on cognition due to elastic band strength training. The aim of this study was to investigate the effects of streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
69
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 80 publications
(84 reference statements)
10
69
2
1
Order By: Relevance
“…In fact, previous data with elderly individuals showed that twenty-eight weeks of exercise intervention was more effective in increasing IL-10 levels rather than decreasing TNF-α levels (Chupel et al 2017). This effect may be mediated by an increase of production and release of anti-inflammatory cytokines by the repeated bouts of exercise from muscle (myokines), or reduced expression of Toll-like receptors in monocytes and macrophages (Gleeson et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, previous data with elderly individuals showed that twenty-eight weeks of exercise intervention was more effective in increasing IL-10 levels rather than decreasing TNF-α levels (Chupel et al 2017). This effect may be mediated by an increase of production and release of anti-inflammatory cytokines by the repeated bouts of exercise from muscle (myokines), or reduced expression of Toll-like receptors in monocytes and macrophages (Gleeson et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, male and female hormones modulate the immune system differently, thus resulting in differential age‐related pathologies . Therefore, muscle strength might be particularly important for women in regulating chronic inflammation …”
Section: Discussionmentioning
confidence: 99%
“…The baseline levels of PF in the participants of this study are better than other investigations in elderly population (6,13) . There was a substantial influence of this type of exercise on strength, aerobic resistance, dynamic balance, and other parameters who contribute significantly to increase the physical autonomy of elderly population (29) .…”
Section: Discussionmentioning
confidence: 54%
“…There was a substantial influence of this type of exercise on strength, aerobic resistance, dynamic balance, and other parameters who contribute significantly to increase the physical autonomy of elderly population (29) . Other studies involving institutionalized elderly population showed that even exercise using elastic bands can increase PF significantly (13) . The same authors showed that even the maintenance of some PF parameters in elderly is a solid benefit in comparison who those that are sedentary and impair their physical condition over time.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation